Benchmarking the Interactions among Challenges for Blockchain Technology Adoption: A Circular Economy Perspective - Anupama Panghal; Shilpa Sindhu; Shweta Dahiya; Bharat Dahiya; Rahul S. Mor (International Journal of Mathematical, Engineering and Management Sciences, 2022)
The chances of food contamination and spoilage get enhanced as it passes through various stages, and prudent consumers often need transparency on the origin of food products, their production and processing facilities utilized. Blockchain, an emerging digital technology, offers food traceability solutions to consumers and supply chain partners. But presently, blockchain adoption in Indian supply chains is in the nascent stages. The present study identified the challenges of adopting blockchain technology in Indian food supply chains and modelled them using Interpretive Structural Modelling (ISM). As per the ISM, the ‘regulatory structure’ and ‘lack of realised need’ emerged as the most significant driving forces that impact other challenges, viz. ‘privacy breach issues’, ‘high costs’, ‘lack of skills’, ‘lack of technology’, ‘lack of trust’ and ‘lack of infrastructure’. These challenges have an impact on the ‘scalability problem’. The paper underlines the significance of enabling regulatory structure, improved information and communication technologies infrastructure, and convincing the supply chain stakeholders to use blockchain technology to resolve the underlying challenges and achieve its adoption and scalability in the Indian food industry.